Leadership - Burns, James MacGregor (New York : Harper & Row, 1978)
The book introduces two types of leadership: transactional leadership, in which leaders focus on the relationship between the leader and follower, and transformational leadership, in which leaders focus on the beliefs, needs, and values of their followers.
First Harper Perennial political classics edition published 2010
Includes bibliographical references and index.
lje 8/9/2014
Loans
Keywords: Leadership